Display LED Mekanis Berbasis Mikrokontroler - Andi Fitriati; Muhammad Akil; Arham Anwar (Jurnal Teknologi Terpadu, 2016)
Generally, a display LED which can display character in large numbers and needs many LEDs too. The aim of this research is to make display LED using 16 LEDs which arranged in horizontal. That display LED is well known in mechanical display LED or propeller LED that can display many characters. The work of mechanical display LED rotates lines of LEDs in high speed and utilizes the speed of LEDs blink alternately, so in the certain speed can form a character letter or number. The method used in this research is a quasi-experimental methods. Basically, this tool utilizes optical phenomenon commonly called Persistence of Vision. Persistence of Vision is the inability of the human eye to see a rapid change of image, so they translate as image sequence. Mechanical LED display is equipped with Infrared remote to give input in real time on the display. Sensor Hall-Effect in Mechanical LED display is used as position of display reference when the display rotates. Input is processed by microcontroller Atmega16A to control LED. The data which received by microcontroller was displayed in 16 LEDs that rotated by DC motor on 2400 rpm speed. Based on the result and observation of the project, the mechanical LED display can display clock using RTC IC. The communication with infrared remote can send well the data at maximum distance of 5 meters without obstructions.